MODEL BANGKITAN PERJALANAN LALU LINTAS PADA ZONA PENDIDIKAN SEKOLAH MENENGAH ATAS NEGERI JEMBER - Yudo Fataroh; Willy Kriswardhana; Nunung Nuring Hayati (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2020)
The increase in facilities and the academic community experienced at 5 Public High Schools in Jember is in line with the increase number of vehicles. The increasing number of vehicles causes traffic jams on the surrounding areas of school. Moreover, most of the parents accompanying their children stop or park their vehicles on the road side. Therefore, it needs a traffic management to solve the problem. The first thing to do is the analysis and modeling of trip generation. Analysis of trip generation modeling in this study was modeled using multiple linear regression methods. The best model produced to predict the trip attraction of Jember Public High Schools vehicles is Y = (0,194) X1 + (1,059) X6 + (42,676) X7 606,109 with an R2 value of 0.945. Meanwhile, the trip production of Jember Public High Schools vehicles is Y = (0.234) X1 + (0.699) X6 + (40,566) X7 594.67 with an R2 of 0.933; where the Y is the number of vehicles, X1 is the number of students, X6 is the class area, and X7 is the ratio of the number of students to teachers.